Tinjauan Kinerja Rantai Pasok - Dyas Marsa Pranoto; Ade Momon S (Peneliti.net, 2022)
Supply Chain Managament is one of the management sciences that discusses a lot about how the company’s efforts to promote it’s suppliers as part of it’s production process. Departing from this, a research was conducted to measure the performance of Supply Chain Management at PT.Pindo Deli Pulp and Paper Mills-3. Therefore, the measurement of the performance of Supply Chain Management at PT.Pindo Deli Pulp and Paper Mills-3 with performance indicators that need to be considered is whether the performance is good or not. If in a Supply Chain Management flow the performance rate is above the average, the it can be concluded that Supply Chain Management flow in the company has been running well so that it has a very positve effect on the production process in a company and if otherwise it is not good, it will be felt the proposed improvement to make the flow of Supply Chain Management in the company can run effectivively and efficiently so as to increase the producticity of the company. In this study using descriptive qualitative and quantitave methods and the results obtained that the Supply Chain Management review at PT.Pindo Deli Pulp and Paper Mills-3 based on the results of the anaysis above, it can be concluded that the Supply Chain Management performance is said to be good performance